To solve for \( t \) in the equation:
\[ -10 + 2t = -20 - 16t + 17t \]
First, simplify the right side of the equation:
\[ -20 - 16t + 17t = -20 + t \]
Now the equation looks like this:
\[ -10 + 2t = -20 + t \]
Next, we can isolate \( t \) by first getting all the \( t \) terms on one side and the constant terms on the other side. Subtract \( t \) from both sides:
\[ -10 + 2t - t = -20 \]
This simplifies to:
\[ -10 + t = -20 \]
Now, add 10 to both sides:
\[ t = -20 + 10 \]
Which simplifies to:
\[ t = -10 \]
Thus, the solution for \( t \) is:
\[ \boxed{-10} \]